The Effects of Teamwork on Organizational Commitment Among Operational Staffs of The Faculty of Humanities, Srinakharinwirot University - Yongsripanyarit, Punyisa; Jansem, Anchalee (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2026)
This research article aims to: (1) examine the factors influencing organizational commitment among operational staff; (2) investigate the effects of teamwork on operational staff; (3) compare levels of organizational commitment before and after the teamwork intervention; and (4) assess the satisfaction level of operational staff toward the teamwork activities. This study employed a mixed-methods design, combining survey research—utilizing questionnaires to collect data on factors and levels of organizational commitment—and experimental research, involving a teamwork activity intervention. The participants comprised 28 operational staff members from the Faculty of Humanities, Srinakharinwirot University. Data were analyzed using descriptive statistics, including means, percentage, and standard deviation, as well as inferential statistics via the Dependent Sample t-test to compare pre- and post-intervention results. The findings revealed that: (1) key factors associated with organizational commitment included interpersonal relationships among colleagues, compensation and benefits, and the relationship between administrators and staff, respectively; (2) the effects of teamwork were rated at a high level; (3) the overall level of organizational commitment among operational staff significantly increased after the intervention. Specifically, affective commitment and normative commitment showed statistically significant improvements, while continuance commitment did not show a statistically significant difference; (4) satisfaction with the teamwork activities was rated at the highest level. These findings suggest that teamwork activities can effectively enhance organizational commitment among operational staff, particularly in terms of emotional attachment and normative loyalty. Such improvements contribute positively to staff attitudes and work motivation. Therefore, organizations may utilize these findings as a foundation for developing tools or activities that sustainably promote organizational commitment. Additionally, the results can be adapted to other organizational contexts with similar operational staff characteristics to foster a positive work environment and enhance overall organizational performance.